Optimizing Spare Part Storage Efficiency in the Automotive Sector Using the PDCA Cycle: A Case Study at Manyar Automotive Companies - Shayet, Moh. Erfan Nur; Aslamiyah, Suaibatul (Institut Dirosat Islamiyah Al-Amien Prenduan Sumenep, 2025)
An inefficient spare parts storage system can disrupt the smooth operation of a company, increase logistics costs, and slow down customer service processes in the automotive sector. The purpose of this study is to evaluate the spare parts storage system at Automotif Company Manyar dealership using the PDCA (Plan-Do-Check-Act) approach as a continuous improvement approach. This study uses a descriptive qualitative approach with a case study method. Data was collected through observation, interviews, and documentation studies. The sample in this study used purposive sampling techniques. The results of this study indicate that the causes of inefficiency in the storage system include errors in estimating needs, lack of staff training, and inaccuracies in the spare parts location information system. The implementation of PDCA can effectively and successfully improve the effectiveness of the storage system through the renewal of work procedures, integration of information systems, and regular training for personnel. This study emphasizes the importance of applying a systematic approach to improve warehouse management quality and support the operational efficiency of automotive dealers.